2016
DOI: 10.1038/ngeo2792
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of landfalling typhoons over the northwest Pacific since the late 1970s

Abstract: Intensity changes in landfalling typhoons are of great concern to East and Southeast Asian countries 1 . Regional changes in typhoon intensity, however, are poorly known owing to inconsistencies among di erent data sets 2-8 . Here, we apply cluster analysis to bias-corrected data and show that, over the past 37 years, typhoons that strike East and Southeast Asia have intensified by 12-15%, with the proportion of storms of categories 4 and 5 having doubled or even tripled. In contrast, typhoons that stay over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
241
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 351 publications
(254 citation statements)
references
References 51 publications
(90 reference statements)
13
241
0
Order By: Relevance
“…TC intensity, which is a measure of the near-center peak wind speed, has long been assumed to be the dominant factor in determining TC destructiveness (measured as the potential dissipation index and accumulated cyclone energy) [Camargo and Sobel, 2005;Emanuel, 2005]. Thus, the destructiveness of TCs is projected to increase [Knutson and Tuleya, 2004;Emanuel, 2005;Elsner et al, 2008;Bender et al, 2010;Knutson et al, 2010;Mendelsohn et al, 2012;Mei and Xie, 2016]. Thus, the destructiveness of TCs is projected to increase [Knutson and Tuleya, 2004;Emanuel, 2005;Elsner et al, 2008;Bender et al, 2010;Knutson et al, 2010;Mendelsohn et al, 2012;Mei and Xie, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…TC intensity, which is a measure of the near-center peak wind speed, has long been assumed to be the dominant factor in determining TC destructiveness (measured as the potential dissipation index and accumulated cyclone energy) [Camargo and Sobel, 2005;Emanuel, 2005]. Thus, the destructiveness of TCs is projected to increase [Knutson and Tuleya, 2004;Emanuel, 2005;Elsner et al, 2008;Bender et al, 2010;Knutson et al, 2010;Mendelsohn et al, 2012;Mei and Xie, 2016]. Thus, the destructiveness of TCs is projected to increase [Knutson and Tuleya, 2004;Emanuel, 2005;Elsner et al, 2008;Bender et al, 2010;Knutson et al, 2010;Mendelsohn et al, 2012;Mei and Xie, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the rainbearing East Asian summer monsoon (e.g., Ninomiya and Murakami 1987;Tao and Chen 1987;Ninomiya and Akiyama 1992;Sampe and Xie 2010) exhibits substantial seasonal-interannual variability because of the influence of both tropical forcing (e.g., the El Niño Southern Oscillation; ENSO) and extratropical atmospheric circulation (e.g., mid-latitude atmospheric teleconnections; Wu and Wang 2002;Ding et al 2011;Kosaka et al 2012;He et al 2017;and references therein). In addition to typhoons from the northwestern Pacific (e.g., Mei et al 2015;Mei and Xie 2016), a quasi-stationary Meiyu-Baiu rainband that extends from southeast China to Japan from June to mid-July is critically important for water resources and natural disasters in the regions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the rainbearing East Asian summer monsoon (e.g., Ninomiya and Murakami 1987; Tao and Chen 1987;Ninomiya and Akiyama 1992; Sampe and Xie 2010) exhibits substantial seasonal-interannual variability because of the influence of both tropical forcing (e.g., the El Niño Southern Oscillation; ENSO) and extratropical atmospheric circulation (e.g., mid-latitude atmospheric teleconnections; Wu and Wang 2002;Ding et al 2011;Kosaka et al 2012; He et al 2017; and references therein). In addition to typhoons from the northwestern Pacific (e.g., Mei et al 2015;Mei and Xie 2016), a quasi-stationary Meiyu-Baiu rainband that extends from southeast China to Japan from June to mid-July is critically important for water resources and natural disasters in the regions.Tropical climate variability, such as ENSO, strongly affects the interannual variability of the East Asian summer monsoon through the tropical western North Pacific (TWNP) anticyclone and references therein). K17 found that the interannual variability of summertime AR occurrence over the northwestern Pacific is largely controlled by the preceding-winter ENSO through the Indo-western Pacific ocean capacitor (IPOC) effect (e.g., Xie et al 2009Xie et al , 2016.…”
mentioning
confidence: 99%
“…It is virtually certain that intense tropical cyclone activity has increased in the North Atlantic, since 1970 [3]. Similarly, according to a latest study, typhoons that strike East and Southeast Asia have intensiied by 12-15% since the late 1970s [6].…”
Section: Climate Change: Observed Changes and Their Causesmentioning
confidence: 99%